2020
DOI: 10.3389/fpsyt.2020.602121
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SIRT1, Cytokines, and Metabolic Syndrome in Schizophrenia Patients With Olanzapine or Clozapine Monotherapy

Abstract: Objective: Previous studies consistently showed the interaction between Sirtuin 1 (SIRT1) and immune inflammation is significantly related to metabolic abnormalities, but their role in the pathogenesis of metabolic syndrome caused by second-generation antipsychotics (SGAs) in schizophrenia patients largely remains unknown. Hence, the present study aimed to fill this gap.Methods: A total of 54 schizophrenia patients with olanzapine or clozapine monotherapy [metabolic syndrome (MetS)/non-MetS patients, 27/27] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Recently, Arabska et al ( 46 ) reported that serum levels of IL-6 and TNF-α in schizophrenia patients were not significantly different with respect to healthy subjects. Significantly higher plasma levels of IL-6, IL-10, and TNF-α were, however, detected in schizophrenia patients treated with olanzapine or clozapine, as compared with normal controls ( 47 ).…”
Section: Cytokines In Schizophreniamentioning
confidence: 99%
“…Recently, Arabska et al ( 46 ) reported that serum levels of IL-6 and TNF-α in schizophrenia patients were not significantly different with respect to healthy subjects. Significantly higher plasma levels of IL-6, IL-10, and TNF-α were, however, detected in schizophrenia patients treated with olanzapine or clozapine, as compared with normal controls ( 47 ).…”
Section: Cytokines In Schizophreniamentioning
confidence: 99%
“…Additionally, a study examining immuno-metabolic profiles identified five cytokines associated with MetS in schizophrenia, including IL-6 and TNF-α 35 . Zhang et al reported that higher plasma IL-6 levels in schizophrenia patients treated with olanzapine or clozapine and with MetS compared to patients without MetS 36 . However, our study did not yield comparable findings for IL-6, potentially attributed to our specific focus on the CR-TRS population.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines play vital roles in the pathogenesis of IR and MS. Patients with MS have higher blood levels of IL-6, 33 TNF-α, 34 and IL-1β. 35 Chronic IL-6 exposure led to IR and related metabolic disorders in a murine model.…”
Section: Discussionmentioning
confidence: 99%